2012
DOI: 10.1016/j.neuropsychologia.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Similar alterations in brain function for phonological and semantic processing to visual characters in Chinese dyslexia

Abstract: Dyslexia in alphabetic languages has been extensively investigated and suggests a central deficit in orthography to phonology mapping in the left hemisphere. Compared to dyslexia in alphabetic languages, the central deficit for Chinese dyslexia is still unclear. Because of the logographic nature of Chinese characters, some have suggested that Chinese dyslexia should have larger deficits in the semantic system. To investigate this, Chinese children with reading disability (RD) were compared to typically develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 54 publications
3
47
1
Order By: Relevance
“…Alternatively, the lack of specialization in the left IFG in the current study might be due to a low sensitivity of the specific task or analyses used in this study. It could be that a more demanding task or a different analysis approach, such as a multi-variate parametric analysis (MVPA), could reveal a double-dissociation between phonological- and semantic-related activation within the left IFG in preschool children, as demonstrated in school-age children (Bach et al, 2010; Cao et al, 2009; Liu et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the lack of specialization in the left IFG in the current study might be due to a low sensitivity of the specific task or analyses used in this study. It could be that a more demanding task or a different analysis approach, such as a multi-variate parametric analysis (MVPA), could reveal a double-dissociation between phonological- and semantic-related activation within the left IFG in preschool children, as demonstrated in school-age children (Bach et al, 2010; Cao et al, 2009; Liu et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the double-dissociation between phonological-related (rhyming judgment) and semantic-related (meaning judgment) tasks in school-age children using visual stimuli (Bach et al, 2010; Cao et al, 2009; Landi et al, 2010; Liu et al, 2012). The study in English (Landi et al, 2010) used a mixed stimuli presentation (orthographic and pictorial) and found greater semantic-related activation in the left STG and AG, as compared to phonological-related activation.…”
Section: Introductionmentioning
confidence: 99%
“…The holistic encoding hypothesis proposes that Chinese characters, despite their diverse stroke patterns, are holistically encoded as a whole perceptual unit involving no independent, intermediate representations of sub-character components (Dehaene et al, 2005;Liu & Perfetti, 2003;Tan et al, 2000;Wong et al, 2012). In support of this idea, previous studies have revealed Chinese-specific engagement of the right visual cortex in addition to its left hemisphere counterpart (Cao et al, 2009;Liu et al, 2012;Tan et al, 2000), which has been shown essential for holistic processing (Kosslyn et al, 1993;Smith et al, 1995). However, the exact functional role of right visual cortex in character recognition remains unclear because this brain system might also be involved in coordination and integration of multiple visual objects given its essential contribution to visuospatial processing (Clements et al, 2006;Corballis, 2003;Ng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Regional BOLD signal change relative to fixation baseline was calculated for each primary condition. Given its essential involvement in Chinese character recognition reported in previous studies, we placed our primary interest in the bilateral visual cortex (Cao et al, 2010;Liu et al, 2012;Siok, Perfetti, Jin, & Tan, 2004;Siok, Spinks, Jin, & Tan, 2009;Tan et al, 2000). However, we did not specifically focus on any specific regions within the visual system, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of Chinese dyslexia have reported reduced activation in bilateral occipito-temporal regions and left middle frontal gyrus (Siok et al, 2004;Siok et al, 2008;Siok et al, 2009), regions not generally found in fMRI studies of dyslexia in alphabetic orthographies. A more recent study demonstrated reduced activation for Chinese dyslexics in right occipital cortex, consonant with a language-specific role of right visual cortex in Chinese reading and suggesting a deficit in holistic visuo-orthographic analysis in Chinese dyslexia (Liu et al, 2012).…”
Section: Making a Hidden Disability Visiblementioning
confidence: 91%